Quality of Snow Cover Characteristics Derived from ERA 5-Land Reanalysis for the Territory of Perm Krai - A. D. Kryuchkov; N. A. Kalinin; I. A. Sidorov (Лëд и снег)
Agreement between values of the mean monthly snow depth provided by the ERA 5-Land reanalysis and similar characteristics of snow cover calculated on the basis of the extended hydrometeorological monitoring performed in the Perm Region for 1990–2020 is analyzed. It was found that ERA 5-Land in 73% of cases reproduces the presence/absence of snow during the onset period, and in 53% – during the period of snow loss. The conclusions made in the authors' previous studies based on more limited material were generally confirmed. It is shown that the reanalysis values of the snow depth are overestimated in relation to instrumental measurements for most of the hydrometeorological stations of the Perm Region. In space, the magnitude of the reanalysis error increases from the southwest to the northeast of the region, with the exception of its central part, where the influence of the Kama water reservoir is perceptible. But the interannual variability of the average snow depth in the Perm Region was reproduced by the ERA 5-Land reanalysis adequately. For 30 years, the magnitude of the reanalysis error decreased as it was compared with 61% observation points. The analysis of seasonal variability showed that in ERA 5-Land time of the maximum snow depth was shifted to earlier onset. The complete coincidence of the seasonal course was recorded only in 5% of hydrometeorological monitoring sites. The value of the average monthly discrepancies between the data of the reanalysis and the information of the posts as a whole exceeds the similar characteristic for the stations, which is especially evident during the period of active snowmelt.